2014
DOI: 10.1002/2014jb011084
|View full text |Cite
|
Sign up to set email alerts
|

Crustal deformation and stress transfer during a propagating earthquake sequence: The 2013 Cook Strait sequence, central New Zealand

Abstract: The 2013 Cook Strait earthquake sequence began on 18 July 2013 with two foreshocks of Mw 5.7 and Mw 5.8 and culminated in the Mw 6.6 Cook Strait and Lake Grassmere events on 21 July and 16 August, respectively. Located ∼50 km south of New Zealand's capital, Wellington, the earthquakes generated the most significant ground shaking in the Wellington and Marlborough regions in recent decades. During the first event, located under Cook Strait, continuously recording GPS instruments across central New Zealand recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 59 publications
1
38
0
1
Order By: Relevance
“…Aftershocks follow a broad NE-SW trend proximal to the Humps and Hundalee faults for ~80 km extending offshore near Kaik ura (Figure 1, S1). The aftershocks then step north, approximately following the Jordan Thrust and Kekerengu faults, with a large cluster of events occurring in the Cape Campbell and Lake Grassmere area (Figure 1), the site of a Mw 6.8 earthquake in 2013 (27). Regional moment tensors (28) for aftershocks show a mixture of reverse and strike slip mechanisms with the majority of events occurring in the upper 20 km ( Figure S1).…”
Section: The 14 Th November 2016 Kaik Ura Earthquakementioning
confidence: 99%
“…Aftershocks follow a broad NE-SW trend proximal to the Humps and Hundalee faults for ~80 km extending offshore near Kaik ura (Figure 1, S1). The aftershocks then step north, approximately following the Jordan Thrust and Kekerengu faults, with a large cluster of events occurring in the Cape Campbell and Lake Grassmere area (Figure 1), the site of a Mw 6.8 earthquake in 2013 (27). Regional moment tensors (28) for aftershocks show a mixture of reverse and strike slip mechanisms with the majority of events occurring in the upper 20 km ( Figure S1).…”
Section: The 14 Th November 2016 Kaik Ura Earthquakementioning
confidence: 99%
“…The NIF is a Kalman filter‐based method that allows us to investigate in detail the timing and location of SSE slip‐rate changes after the Eketahuna earthquake. Prior to running the NIF, we correct the cGPS time series for small coseismic displacements observed at some nearby cGPS sites during the 20 January Eketahuna earthquake, as well as coseismic displacements from Hamling et al [] for a sequence of earthquakes in Cook Strait in June/July 2013.…”
Section: Kapiti Sse Evolution and Temporal Relationship To A Nearby Imentioning
confidence: 99%
“…Using InSAR (interferometric synthetic aperture radar),Hamling et al (2015) have shown potential movement along this fault during the 2004-2005 Manawatu SSE. We also note that the earthquakes in Upper Hutt 2004-2005, Masterton 2010 and the M L >5 earthquake further north along the Wellington fault during the Manawatu 2004-2005 SSE all have broadly similar, normal, CMT solutions.…”
mentioning
confidence: 99%